Factors Affecting Lowland Rice Production In Lawada Jaya Village, Sawerigadi District, West Muna Regency - Hernica ninawarni; Surni Surni; Abdul Gafaruddin (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this research is to find out the factors that influence the production of lowland rice farming in Lawada Jaya Village, Sawerigadi District, West Muna Regency. This research was conducted in Lawada Jaya Village, Sawerigadi District, West Muna Regency. Respondents were 26 people, which was done by simple random sampling method. Analysis of the data used is multiple linear regression analysis. Data analysis using Cobb-Douglas, then the equation is in the form of natural logarithms to facilitate multiple linear regression analysis using SPSS software. The results of this study indicate that the influential or significant production factors are land area and seeds. While the production factors that do not significantly affect the production of lowland rice are labor and fertilizers.